(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
The Ohmic heating behavior and electrical property of the carbon fabric/green epoxy composite laminates filled with various concentrations of unmilled fly ash and milled fly ash were investigated in present work. We used an infrared camera to record the change in surface temperature of composites over a period of time by varying the voltage from 0 to 10 V. The results show that the composite containing low concentration of fly ash exhibited the optimum Ohmic heating behavior under different applied voltages. The maximum temperatures of epoxy/carbon composites were adjustable by controlling the concentrations of fly ash fillers as well as the applied voltage. When a certain voltage was applied to the composite, the surface temperature of composite raised to the maximum within 20 s and became stable, then cool down to room temperature in 120 s. In addition, the milled fly ash filled epoxy/carbon composites were found to reveal improvement in electrical heating performance and structural stability over the unmilled fly ash filled composites.